OPTIMALISASI SKEMA BAGI HASIL SEBAGAI SOLUSI PERMASALAHAN PRINCIPAL-AGENT DALAM PEMBIAYAAN MUDHARABAH PADA PT.BANK MUAMALAT INDONESIA CABANG MATARAM - Siti Rizqi Aulia; Takdir Jumaidi; Akram Akram (Jurnal Riset Akuntansi, 2018)
The objective of this is study to determine the measures taken by the Mataram branch of PT. Bank Muamalat Indonesia in optimizing the profit sharing scheme that can be a solution to the problem of agency, namely adverse selection and moral hazard in mudharabah financing, as well as things that are considered by banks and customers in determine the ratio of portion for the profit sharing. This research is a descriptive study. Sample of the study consist of employees of the Mataram branch of PT. Bank Muamalat Indonesia and customer of mudharabah financing. Data were obtained through the distribution of questionnaires, interviews and observations. Analyses based on validity test, reliability test and description of the percentage scores from the questionnaire showed that in optimizing the profit-sharing scheme, the Mataram branch of Bank Indonesia Mumalat negotiate profit sharing with the mudharabah financing customers. Matters considered by the bank and its customers when negotiating profit sharing ratio are: (1) Estimation of the profit margin business (2) Consideration on the financing period (3) Estimation on every month or each transaction of sales volume. (4) Estimation on every month or each transaction selling price fluctuations (5) Estimation on net profit of each sale transaction. (6) Estimation on cost of goods sold the business (7) Estimation on the percentage/portion of profit sharing to customers/investors/depositors. (8) the desired level of profit projections. Meanwhile, in order to minimize agency problems the bank should: (1) disburse financing with very selective procedure. (2) conduct monitoring after the business is running (3) determine the rate of profit sharing ratio as expected by customer which can encourage customer in increasing the level of its efforts in running the business (4) preserve a pledge that encourage customers to be serious about doing their business. To overcome the problem of adverse selection that is before the financing is granted, the bank should provides a more stringent requirement that the customer should previously had been a customer of Bank Muamalat Indonesia with contract other than the mudharaba contract and a minimum period of 3 years. This is necessary in order to look at the track record of the prospective customers. Meanwhile, to address the moral hazard problem that is after the financing is granted, the bank routinely monitors its customer, both actively and passively. Active monitoring involves visiting customers on a regular basis and passive monitoring is done by monitoring payment obligation of the client to the bank in every end of the month.